Estrategias metodológicas activas y la lecto-escritura, en la Asignatura de Lengua y Literatura, del Quinto grado “A”, Escuela “Miguel Riofrío”, Loja 2021- 2022. - Japón Cabrera, Natalia Cristina (2022)
The present Curriculum Integration work called: Active methodological strategies and reading-writing in the Language and Literature Subject, had a general objective: Contribute to the improvement of the teaching and learning process of reading-writing of fifth-grade students of the "Miguel Riofrío" Basic Education school, in the city of Loja, through active methodological strategies. As specific objectives were proposed: Identify active methodological strategies that help improve the learning of reading-writing in fifth-grade students of the "Miguel Riofrio" Basic Education School; Likewise, to determine the difficulties that students present in the teaching and learning process of reading-writing in the Language and Literature Subject; and develop a proposal that helps improve the teaching and learning process of reading-writing in fifth-grade students, through active methodological strategies to generate meaningful learning. The present investigation was of a descriptive type with a mixed approach and non-experimental design. In addition, methods such as: scientific, observational, hermeneutical, and statistical, techniques such as direct observation and survey, and instruments such as the direct observation guide and the questionnaire. Finally, the population was the "Miguel Riofrío" school and the sample was the teacher and the fifth-grade students "A" for which a non-probabilistic sample was used. After the study, it is determined that the teacher uses active methodological strategies for teaching reading-writing. Also, the problems presented by students are related to reading-writing. Therefore, a "didactic guide" was proposed, with dynamic activities to improve this learning through active methodological strategies. Keywords: Methodological strategies, reading-writing, Language and Literature, Ludic Strategy.